An Investigation on the role of crystallographic texture on anisotropic electrochemical behavior of a commercially pure nickel manufactured by laser powder bed fusion (L-PBF) additive manufacturing. (10th September 2020) - Torbati-Sarraf, H.; Ghamarian, I.; Poorganji, B.; Torbati-Sarraf, S.A.
Abstract: The layer-wise deposition of the laser powder bed fusion (L-PBF) process offers a tailorable microstructure with anisotropic properties. This research aimed to investigate the contribution of crystallographic texture on the anisotropic electrochemical/corrosion behavior of a L-BPF processed commercially pure nickel (Ni) cube along surfaces oriented parallel and perpendicular to the building direction. In order to exclusively assess the role of crystallographic texture on the corrosion behavior, the electrochemical measurements were performed on different surfaces of the L-PBF processed cube in alkaline and acidic chloride-free solutions. Orientation microscopy analysis showed that the morphology of grains along the parallel surface to the building direction was columnar, and their crystallographic orientation distribution was uniform. In contrast, the morphology of grains on the surface aligned normal to the building direction was equiaxed and highly oriented toward [110] . This bias in the orientation distribution led to the highest residual affinity for oxidation in comparison to the other planes in the FCC (Face Centered Cubic) crystal structure. In the case of 1 M NaOH solution, the hydroxide layer formed at the exposed surface did not effectively control the cation ejection from the surface. Also, surfaces oriented normal to the building direction, with lower surface atomic density, showed an elevated dissolution rate. Conversely, in the case of 1 M H2 SO4 solution, a more integrated and thicker oxide film formed in comparison to the surface aligned parallel to the building direction. This fact led to reduced surface dissolution. This study shows that engineering the topology and microstructure based on the desired properties can remarkably promote the performance of additively manufactured materials in extreme environments.